An interactional "live eye tracking" study in autism spectrum disorder: combining qualitative and quantitative approaches in the study of gaze. Issue 3 (3rd July 2017) - Dindar, Katja; Korkiakangas, Terhi; Laitila, Aarno; Kärnä, Eija
ABSTRACT: Recent studies on gaze behaviours in individuals with autism spectrum disorder (ASD) have utilised "live eye tracking." Such research has focused on generating quantitative eye tracking measurements, which provide limited (if any) qualitative contextual details of the actual interactions in which gaze occurs. This article presents a novel methodological approach that combines live eye tracking with qualitative interaction analysis, multimodally informed conversation analysis . Drawing on eye tracking and wide-angle video recordings, this combination renders visible some of the functions, or what gaze "does, " in interactional situations. The participants include three children with ASD and their adult co-participants during body-movement gaming sessions. The article demonstrates how quantitative eye tracking research can be extended qualitatively using a microanalytic interaction analysis to recontextualise the gaze shifts identified. The findings in this article show that the co-participants treat a child's gaze shifts differently depending on when these occur in a stream of other action. The study suggests that introducing this qualitative dimension to eye tracking research could increase its ecological validity and offer new insight into gaze behaviours in ASD.